Analysis of temperature increase impact on oxygen depletion - Lebelo, RS; Langa, MH; Adesanya, SO; Kaeane, NL (International Journal of Innovative Research and Scientific Studies, 2025)
One of the significant challenges in urbanization and industrialization is the release of harmful reactive contaminants that undergo exothermic chemical reactions into drinking water sources. This challenge is of interest even to the United Nations in ensuring clean water, environments free of hazardous material, and good health. In this article, a mathematical examination of the heat generation due to exothermic chemical reaction in water is conducted on the dissolved oxygen level for aquatic life and the emergence of dangerous bacteria and algae that could trigger water-related diseases. The study compares the temperature rise in a one-step (includes one activation energy profile), two-step (includes two activation energy profiles), and three-step (includes three activation energy profiles) exothermic chemical reactions to observe how the oxygen depletion rate occurs accordingly. The appropriate equations governing the heat and mass transfer within the cylindrical channel are formulated, presented in dimensionless form, and solved numerically using the Runge-Kutta Fehlberg method in conjunction with the Shooting technique. The results indicate that the oxygen depletion in a one-step exothermic chemical reaction is less than in the two-step reaction and is highest in the three-step condition, as the temperature increase strength is observed from one-step to three-step situation. Moreover, the results show that the temperature intensity becomes stronger as the reaction mechanism steps increase from one to three.